2017
DOI: 10.1016/j.cell.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Massively Parallel Biophysical Analysis of CRISPR-Cas Complexes on Next Generation Sequencing Chips

Abstract: Summary CRISPR-Cas nucleoproteins target foreign DNA via base pairing with a crRNA. However, a quantitative description of protein binding and nuclease activation at off-target DNA sequences remains elusive. Here, we describe a chip-hybridized association-mapping platform (CHAMP) that repurposes next-generation sequencing chips to simultaneously measure the interactions between proteins and ~107 unique DNA sequences. Using CHAMP, we provide the first comprehensive survey of DNA recognition by a Type I-E CRISPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 50 publications
12
139
0
Order By: Relevance
“…To understand how Cascade participates in both interference and primed acquisition, we imaged fluorescent Tfu Cascade on double-tethered DNA curtains that extend the substrate in the absence of buffer flow (Gallardo et al, 2015; Jung et al, 2017) (Figure 1 and S1). The DNA substrate lacked a target DNA sequence that was complementary to the Cascade crRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how Cascade participates in both interference and primed acquisition, we imaged fluorescent Tfu Cascade on double-tethered DNA curtains that extend the substrate in the absence of buffer flow (Gallardo et al, 2015; Jung et al, 2017) (Figure 1 and S1). The DNA substrate lacked a target DNA sequence that was complementary to the Cascade crRNA.…”
Section: Resultsmentioning
confidence: 99%
“…For fluorescent labeling, the Cas6e subunit encoded a 3xFLAG epitope tag (Jung et al, 2017). TfuCse1 variants with mutated positive patch residues were cloned by using QuickChange multi-site mutagenesis (Agilent) using oligos MB75, MB76, MB77 & MB78 and MB79 & MB80 for Cse1(5A) and Cse1(3R) respectively (Table S1).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Previous studies have shown that Cascade binds promiscuously to targets with a variety of non-canonical “functional” PAM sequences (Jung et al, 2017; Leenay et al, 2016; Xue et al, 2015), and dsDNA target contains functional PAMs throughout the sequence (Table S3). Therefore, it is possible that the broad FRET distribution observed for non-targeting Cascade may be due to Cascade binding promiscuously at functional PAM sequences, rather than at random non-specific sites.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that the broad FRET distribution observed for non-targeting Cascade may be due to Cascade binding promiscuously at functional PAM sequences, rather than at random non-specific sites. To address this possibility, we designed three dsDNA substrates containing 0, 1 or 3 canonical 5′-AAG-3′ PAM sequences (dsDNA 0PAM , dsDNA 1PAM and dsDNA 3PAM , respectively), and otherwise consisting mainly of 5′-CCG-3′ triplets, a well-characterized non-functional PAM motif (Fineran et al, 2014; Jung et al, 2017; Leenay et al, 2016; Westra et al, 2012; Xue et al, 2015) (Table S3). Similar to non-targeting Cascade binding to dsDNA target , individual FRET trajectories for these three substrates revealed transient FRET events (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation